Development prospects of “Internet + medical and health services” in Shandong: application status and public acceptance - Gao, YingJie; Wang, YaQiong; Yan, XiaoLin; Sun, GuanNan; Chen, Cong; Gao, Xiang (Frontiers in Public Health, 2025)
BackgroundThe integration of Internet technology into healthcare has led to the birth of the “Internet + medical and health services” model-a transformative approach to improving accessibility and efficiency in healthcare delivery.ObjectiveThis study aims to assess the current status, challenges, and user perceptions of the “Internet + medical and health” services platform among individuals in Shandong, China.MethodsThe cross-sectional survey was conducted between September 2023 and October 2023 on patients from public medical institutions in Shandong Province. A structured questionnaire was employed to gather information on the general characteristics of the respondents and information about platform usage and user experiences.ResultsOf the 400 distributed questionnaires, 353 were valid. Most respondents were female (59.38%), aged 31–35 (28.13%), and held a bachelor's degree (55.97%). Compared to the educational distribution in the census results, individuals with a bachelor's degree or equivalent were significantly overrepresented in the surveyed population (16% vs. 69.61%, p < 0.001). Key barriers included a preference for face-to-face consultations (18%) and data security concerns (15%). Respondents emphasized the need for clearer legal regulations (4.33 ± 0.73) and greater public awareness (4.23 ± 0.68).ConclusionsPeople with higher education levels are more likely to adopt Internet Plus healthcare services, noting the hospital-affiliated platforms as their most-used types. While users appreciate the benefits of digital healthcare, concerns regarding personal information security and regulatory clarity continue to obstruct their wider use. Boosting data security, developing legal frameworks, and increasing user education should be the three central areas of improvement to facilitate a greater degree of acceptance and successful implementation of Internet Plus healthcare services.